IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA LAHAT - Resty Seftiany; Wita Hariani; Trecy Austin (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
Poverty remains a significant social problem in Lahat City, as it directly affects the quality of life of the community. The local government has implemented various poverty alleviation policies; however, their implementation has not yet achieved optimal outcomes. This study aims to examine the implementation of poverty alleviation policies in Lahat City by analyzing data collection processes, aid distribution mechanisms, the role of implementing officials, and the impact of policies on the social and economic conditions of poor communities. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, field observations, and documentation involving local government officials, program beneficiaries, and community leaders. The findings indicate that poverty alleviation policies in Lahat City have provided tangible benefits, particularly through social assistance programs and the fulfillment of basic needs. Nevertheless, policy effectiveness is constrained by inaccurate beneficiary data, limited budget allocation, and weak coordination among related institutions. Conversely, strong commitment from the local government, active involvement of frontline officials, and support from community leaders serve as important supporting factors. This study concludes that improving data accuracy, strengthening institutional coordination, and developing long-term economic empowerment programs are essential to enhance the effectiveness and sustainability of poverty alleviation policies in Lahat City.